Isobavachalcone From Cullen corylifolium Presents Significant Antibacterial Activity Against Clostridium difficile Through Disruption of the Cell Membrane - Liu, Xi-Wang; Yang, Ya-Jun; Qin, Zhe; Li, Shi-Hong; Bai, Li-Xia; Ge, Wen-Bo; Li, Jian-Yong (Frontiers in Pharmacology, 2022)
Background:Clostridium difficile infection (CDI) has been widely reported in human and animals around the world over the past few decades. The high relapse rate and increasing drug resistance of CDI make the discovery of new agents against C. difficile fairly urgent. This study aims to investigate the antibacterial activity against C. difficile from traditional Chinese herb medicine Cullen corylifolium and confirm its active components. Methods: Phenolic extract from the seeds of C. corylifolium was prepared routinely and the contents of relative flavonoids were determined by High Performance Liquid Chromatography (HPLC). In vitro antibacterial activities of the phenolic extract and its major components were tested. The influence of the major components on cell membrane was investigated with membrane integrity by SEM and propidium iodid uptake assay. Cytotoxicity of the extract and its active compounds on Caco-2 cell line was assessed by CCK-8 kit. The in vivo therapeutic efficacy of IBCL was evaluated on the mice model. Results: Phenolic extract was found to be active against C. difficile with minimum inhibitory concentrations (MIC) of 8 μg/mL. As the major component of the extract, IBCL was the most active compound against C. difficile. The MIC of IBCL and 4MBCL were 4 μg/ml and 4 μg/ml, respectively. Meanwhile, PFPE, IBCL, and 4MBCL showed rapid bactericidal effect against C. difficile in 1 h, which was significant compared to antibiotic vancomycin. Mechanism studies revealed that IBCL can disrupt the integrity of the cell membrane, which may lead to the death of bacteria. PFPE was low cytotoxic against Caco-2 cells, and the cytotoxicity of IBCL and 4MBCL were moderate. Symptoms of CDI were effectively alleviated by IBCL on the mice model and weight loss was reduced. From death rates, IBCL showed better efficacy compared to vancomycin at 50 mg/kg dosage. Conclusion: As the major component of phenolic extract of C. corylifolium seeds, IBCL showed significant antibacterial activity against C. difficile in vitro and rapidly killed the bacteria by disrupting the integrity of the cell membrane. IBCL can significantly prevent weight loss and reduce death caused by CDI on the mice model. Therefore, IBCL may be a promising lead compound or drug candidate for CDI.